Oral health-related quality of life in type 2 diabetic patients of Yogyakarta General Hospital - Dewi Agustina; Nunuk Purwanti; Lisdrianto Hanindriyo; Fimma Naritasari (Faculty of Dentistry, Universitas Gadjah Mada, 2021)
Yogyakarta is a province in Indonesia with the highest prevalence (2.4%) of Diabetes Mellitus (DM). Around 90% of diabetic patients suffer from type 2 DM. Oral manifestations of DM may disturb oral functions which in turn influence oral health - related quality of life (OHRQo)L. This study aimed to evaluate the OHRQoL of type 2 DM outpatients in Yogyakarta General Hospital. The study subjects comprised 50 male outpatients and 32 female outpatients with type 2 DM (40-81 years old). Geriatric Oral Health Assessment Index (GOHAI) and Xerostomia Inventory were used to assess OHRQoL and xerostomia status, respectively. Intraoral examinations comprising periodontal tissue, oral hygiene (OH), coated tongue, and present teeth were performed. There were 49 (59.76%) subjects with low and 33 (40.24%) subjects with high score of GOHAI; 78 (95.12%) with and 4 (4.88%) without periodontal tissue defect; 79 (96.34%) with poor and 3 (3.66%) good OH; 17 (20.73%) with coated tongue >50% and 65 (79.27%) with coated tongue ≤50%; 34 (41.46%) with present teeth <20 and 48 (58.54%) with present teeth ≥20; and 39 (47.56%) with xerostomia and 43 (52.44%) with normal status. Only ‘present teeth’ had a significant contribution to the proportion of GOHAI status in type 2 DM patients in this study (p=0.032). Type 2 DM patients with ≥20 teeth had a more significant proportion of high GOHAI status compared to those with <20 teeth. The majority of type 2 DM outpatients of Yogyakarta General Hospital had poor OHRQoL as reflection of their oral condition that is partly contributed by patients with present teeth <20.